Antibiotic prophylaxis in digestive endoscopy: Guidelines from the French Society of Digestive Endoscopy - Karsenti, David; Gincul, Rodica; Belle, Arthur; Vienne, Ariane; Weiss, Emmanuel; Vanbiervliet, Geoffroy; Gronier, Olivier (Endoscopy International Open, 2024)
Digestive endoscopy is a highly dynamic medical discipline, with the recent adoption of new endoscopic procedures. However, comprehensive guidelines on the role of antibiotic prophylaxis in these new procedures have been lacking for many years. The Guidelines Commission of the French Society of Digestive Endoscopy (SFED) convened in 2023 to establish guidelines on antibiotic prophylaxis in digestive endoscopy for all digestive endoscopic procedures, based on literature data up to September 1, 2023. This article summarizes these new guidelines and describes the literature review that fed into them.
Keywords: Endoscopic ultrasonography; Endoscopy Upper GI Tract; Endoscopy Lower GI Tract; Pancreatobiliary (ERCP/PTCD); Quality and logistical aspects; Quality management